An Appraisal of the Plate Tectonic Forces: Role of Gravitational Potential Energy (GPE) in the Deformation of Indo-Eurasian Collision Zone - Reddy, C.D.; Shrivastava, Mahesh N. (My University, 2017)
Concording with the plate tectonic theory, lithosphere consists of several tectonic plates moving in different directions and stimulating various tectonic processes and consequencing mountains, earthquakes, volcanoes, mid-oceanic ridges and oceanic trenches. It is excogitated that three main plate tectonics driving forces viz. ridge push, slab pull and trench suction together with resistance force viz. collisional resistance, basal drag etc. maneuvering deformation in Indo-Eurasian collision region. But these forces acting in tandem are not sufficient in explaining the discrepancies in regional surficial lithospheric deformation pattern explicitly. Hence, we invoke Gravitation Potential Energy (GPE) derived deviotoric stress in explaining the deformation pattern of Indo-Eurasian collision region. We also provide explanation for the occurrence of Mw 7.3 aftershock following the 2015 Mw 7.9 Nepal earthquake construing the GPE as an important proxy to the deviatoric stress field.
Keywords: Tectonic forces; Topography; GPE; Indo-Eurasian; Himalaya; Deformation